Enantioselective regiospecific addition of propargyltrichlorosilane to aldehydes catalyzed by biisoquinoline N,N’-dioxide - Noble Brako; Sreerag Moorkkannur Narayanan; Amber Burns; Layla Auter; Valentino Cesiliano; Rajeev Prabhakar; Norito Takenaka (Beilstein Journal of Organic Chemistry)
Distilled propargyltrichlorosilane with >99% isomeric purity was prepared for the first time, and its asymmetric catalytic regiospecific addition reaction to aldehydes was developed through a systematic catalyst structure–reactivity and selectivity relationship study. The observed catalyst structure–enantioselectivity relationship of the present allenylation reaction was found exactly opposite to that of the analogous allylation reaction. The method provided eleven α-allenic alcohols in 22–99% yield with 61:39–92:8 enantiomeric ratios. Furthermore, possible mechanisms of propargyl–allenyl isomerization of propargyltrichlorosilane were computationally investigated.